Pengaruh Kualitas Laba, Tax Planning dan Kebijakan Dividen terhadap Nilai Perusahaan dengan Green Accounting sebagai Pemoderasi - Suhendra, Suhendra; Tambun, Sihar; Sumarsam, Weni (Media Akuntansi Perpajakan, 2025)
The aim of this research is to test and analyze the influence of earnings quality, tax planning, dividend policy on company value with green accounting as a moderator. The sample used in this research is property sector companies listed on the Indonesia Stock Exchange (BEI) during the 2020 – 2023 period. The research methodis panel data regression. The supporting grand theories in this research are agency theory, signal teory and bird in the hand teory. The earning quality variable is proxied by ratio of cash from operations to nett income. Tax planning is proxied by the cash Effective Tax Ratio (CETR). Dividend policy is proxied by the Dividend payout Ratio (DPR). Company Value proxied by price Book Value (OBV). Green accounting is proxied by the environmental cost ratio. The results of the research show that profit quality has a negative effect on company value, tax planning has a positive on company value, Dividend Policy has a negative effect on company Value, Green Accounting moderation strenghthens that negative effect of profit quality on company value, green accounting moderation strenghthens the positif effect of tax planning on company value, green accounting moderation strengthens the negative effect of dividend policy on company value.